Impact of diabetes on the natural history of tuberculosis - Restrepo, Blanca I. (Diabetes Res Clin Pract, 2014)
Tuberculosis (TB) is the number one bacterial killer worldwide and the current increase in type 2 diabetes mellitus patients (DM), particularly in countries where TB is also endemic, has led to the re-emerging importance of DM2 as a risk factor for TB. There is an urgent need to implement strategies for TB prevention among the millions of DM patients exposed to Mycobacterium tuberculosis (Mtb) worldwide, but knowledge is limited on how and when DM2 alters the natural history of this infection. In this review we summarize the current epidemiological, clinical and immunologic studies on TB and DM and discuss the clinical and public health implications of these findings. Specifically, we evaluate the mechanisms by which DM patients have a higher risk of Mtb infection and TB development, present with signs and symptoms indicative of a more infectious TB infection, and are more likely to have adverse TB treatment outcomes, including death. Emphasis is placed on type 2 DM given its higher prevalence in contemporary times, but the underlying role of hyperglycemia and of type 1 DM is also discussed.